The Evolution of Political Theatre: A Study of Revolutionary Drama - Ni Wayan Karmini; Ali Khan; Fatima Malik (Yayasan Adra Karima Hubbi, 2024)
Background. Political theater has played an important role in social changes and revolutions in different parts of the world. Purpose. This research aims to explore the evolution of political theater, especially in the context of revolutionary movements, with a focus on the adaptation of staging techniques and local cultural influences. Method. This study uses a descriptive qualitative method with a historical approach and content analysis, which includes political theater scripts from Europe, Latin America, Asia, and Africa. Results. The results of the study show that political theater continues to evolve, especially through the use of interactive techniques and the integration of local cultural elements. The development of digital technology also plays an important role in spreading political messages more widely through online platforms. In non-Western regions, political theater emphasizes traditional arts such as music and dance as part of the delivery of revolutionary messages. Conclusion. In conclusion, political theater remains relevant in the modern era by continuing to adapt to social, political, and technological contexts. This research contributes to the understanding of how political theater functions as a tool for social change, as well as opening up opportunities for further research on the impact of globalization and technology on contemporary political theater.